The Current State of Climate Change Perceptions and Policies in Vietnam: 2014 Report - McKinley J; Adaro, C.; Pede, Valerien O.; Setiyono T; Cong Tran Thanh; Lien Huong D; Trung Kien N; Quicho E; Sheinkman, Michael; Wassmann, Reiner (2015)
This report was constructed to assess the current perceptions and policies regarding climate change in Vietnam. The report comprises a country report, outlining current policies relating to climate change, stakeholder mapping regarding climate change locally and nationally, and results from two stakeholder perception surveys conducted locally and nationally in Vietnam. A total of 50 stakeholders were interviewed, 25 locally and 25 nationally. The stakeholders in the survey represented government offices, universities, research institutions, NGOs, and farmers’ groups. Concerns about climate change impacts included drought, flooding, rainfall variation, and salinity intrusion. These concerns, as well as the methods in which stakeholders would like to receive climate information, varied between local and national stakeholders as well as by the type of institution that the stakeholder represented. This emphasizes a need for location- and user-specific responses to climate change.